The UV and FTIR Fingerprint of Ocimum kilimandscharicum Guerke Essential oil: A Eugenol-Rich Chemo Type - Ayoubi, Rabia; Wali, Sadia; Singh, Gyanesh B (International Journal of Innovative Research and Scientific Studies, 2022)
Ocimum kilimandscharicum Guerke, a member of the family Lamiaceae, is a valuable medicinal plant used both in traditional and modern medicine. It is a perennial aromatic undershrub with tremendous phytochemical polymorphism. The present study aims to assess the amount of eugenol in the essential oil (EO) of O. kilimandscharicum. Eugenol is one of the most popular phenolic compounds, which is naturally synthesized and extracted from the EO of different plant species. The fresh leaves and flowers of O. kilimandsharicum were used to extract EO using a hydrodistillation method. Ultraviolet (UV) and Fourier Transform Infrared (FTIR) spectrometry techniques were used to assess and quantify the chemical fingerprint of the EO and their main phytoconstituents. In this study, eugenol showed its peak absorbance to be around 282 nm in both the EO and pure eugenol spectra. The FTIR spectra of the EO and eugenol showed different functional groups determined by comparing the vibration frequencies in wave numbers of the EO and eugenol spectra with those of an IR correlation chart. Eugenol is a well-known phenolic compound with medicinal and economic value. The UV and FTIR spectra of the EO of O. kilimandsharicum proved the presence of a high amount of eugenol in the O. kilimandscharicum plant.